A Systematic Review on Curcumin and Anti-Plasmodium berghei Effects - Shakib, Pegah; Kalani, Hamed; Ho, Jeffery; Dolatshah, Mehrdad; Amiri, Sana; Cheraghipour, Kourosh (Current Drug Discovery Technologies, 2022)
Background: Turmeric (Curcuma longa L.) is a popular spice containing curcumin that is responsible for its therapeutic effects. Curcumin with anti-inflammatory, antioxidant, anti-cancer, and antimicrobial activities has led to a lot of research focusing on it over the years. This systematic review aimed to evaluate research on the anti-Plasmodium berghei activity of curcumin and its derivatives. Methods: Our study was performed according to PRISMA guidelines and was recorded in the database of a systematic review and preclinical meta-analysis of CAMARADESNC3Rs (SyRF). The search was performed in five databases, namely Scopus, PubMed, Web of Science, EMBASE, and Google Scholar, from 2010 to 2020. The following keywords were searched: “Plasmodium berghei”, “Medicinal Plants”, “Curcumin”, “Concentration”, Animals kind”, “Treatment Durations”, “Routes of Administration” and “in vivo”. Results: Of the 3,500 papers initially obtained, 14 articles were reliable and were thus scrutinized. Animal models were included in all studies. The most commonly used animal strain was Albino (43%), followed by C57BL/6 (22%). The other studies used various murine strains, including BALB/c (14%) and ICR (7%). Two (14%) studies did not mention the strain of animal model used. Curcumin alone or in combination with other compounds depending on the dose used, route of administration, and animal model showed a moderate to strong anti-Plasmodium berghei effect. Conclusion: According to the studies, curcumin has anti-malarial effects on Plasmodium berghei, and, however, its effect on human Plasmodium is unclear. Due to the side effects and drug resistance of current drugs in the treatment of human malaria, the use of new compounds with few or no side effects, such as curcumin, is recommended as an alternative or complementary treatment.
Keywords: parasitic activity